Fuzzy logic-based adaptive decision support in autonomous vehicular networks - Chrysostomou, Chrysostomos; Djouvas, Constantinos; Lambrinos, Lambros (My University, 2014)
The area of intelligent autonomous vehicles and systems poses new challenges in providing mechanisms for efficient communication and control between vehicles, as well as developing robust, adaptive techniques to support intelligent transportation system applications. In this chapter, we show the need for providing an intelligent controller offering decision support in autonomous vehicular networks in terms of broadcast communication channel access. Specifically, we exploit fuzzy logic control, derived from its reported strength of using linguistic information to control nonlinear systems, to build an adaptive, intelligent controller, based on the traffic density, to aid vehicles in deciding when to access the broadcast communication channel. It is demonstrated, by means of enriched simulative evaluation that the fuzzy logic-based controller offers inbuilt robustness with effective control of the system under dense conditions, in contrast with the conventional - IEEE 802.11p standard - solution we compared against.
Keywords: Autonomous vehicular networks; Broadcast communication channel access; Cooperative awareness; Decision support; Fuzzy logic control